2021
DOI: 10.3390/foods10112588
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Consumers’ Attitudes towards So-Called “Cell-Based Meat”

Abstract: The main goal of this online survey was to investigate the attitudes of Brazilians towards “cell-based meat”, which has become the subject of great scientific and media enthusiasm. The answers of 4471 respondents concluded that 46.6% of them thought “cell-based meat” was promising and acceptable. More than 66% would be willing to try this novel product compared to 23% who expressed reluctance to do so. Nearly 40% of the total respondents did not want to eat “cell-based meat” regularly at all, whereas 29%, 43.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 55 publications
(97 reference statements)
4
47
2
2
Order By: Relevance
“…Similarly, a study [ 16 ] that analyzed the various terms used to describe cultured meat reported that “process-centered terms” such as “cell-based”, “cultured”, and “cultivated” were considered to be the most transparent and “free of moral judgment”, while terms such as “lab-grown”, “in vitro”, and “synthetic” were negatively associated with artificiality in consumers’ minds. Other research [ 40 ] reinforced these findings, noting that, when consumers perceive a product as more “high tech”, they are more suspicious of it and less inclined to purchase or consume it.…”
Section: Theoretical Backgroundmentioning
confidence: 84%
See 3 more Smart Citations
“…Similarly, a study [ 16 ] that analyzed the various terms used to describe cultured meat reported that “process-centered terms” such as “cell-based”, “cultured”, and “cultivated” were considered to be the most transparent and “free of moral judgment”, while terms such as “lab-grown”, “in vitro”, and “synthetic” were negatively associated with artificiality in consumers’ minds. Other research [ 40 ] reinforced these findings, noting that, when consumers perceive a product as more “high tech”, they are more suspicious of it and less inclined to purchase or consume it.…”
Section: Theoretical Backgroundmentioning
confidence: 84%
“…Furthermore, analysis of the livestock industry through the lens of economic cost ignores another tangible cost: the impact on the environment and climate. With regard to greenhouse gas emissions [ 27 ], one previous study [ 40 ] noted that the size of the global middle class is rapidly expanding, leading more consumers in developing countries to have an interest in and the means to purchase animal products, including meat; consequently, consumer demand and global food security needs are exerting combined pressures on the livestock industry to produce greater amounts of animal products that are “environmentally sound, socially responsible, and economically viable”.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Une récente étude en France va dans ce sens, puisque la majorité (entre 65,4 et 70,2 % selon les groupes de consommateurs) préfère payer moins cher à beaucoup moins cher la « viande in vitro » par rapport à celle issue d'élevage (Hocquette et al, 2022). Une grande proportion d'indécis est présente dans ces études, et s'explique par le fait qu'une majorité de consommateurs serait prête à goûter le produit une fois, sans en consommer de façon régulière (Wilks et Phillips, 2017 ;Weinrich et al, 2020 ;Chriki et al, 2021).…”
Section: Disposition à Payer Et Influences Culturellesunclassified